Dose estimation derived from the exposure to radon, thoron and their progeny in the indoor environment - Ramola, R. C. (Sci Rep, 2016)
The annual exposure to indoor radon, thoron and their progeny imparts a major contribution to inhalation doses received by the public. In this study, we report results of time integrated passive measurements of indoor radon, thoron and their progeny concentrations that were carried out in Garhwal Himalaya with the aim of investigating significant health risk to the dwellers in the region. The measurements were performed using recently developed LR-115 detector based techniques. The experimentally determined values of radon, thoron and their progeny concentrations were used to estimate total annual inhalation dose and annual effective doses. The equilibrium factors for radon and thoron were also determined from the observed data. The estimated value of total annual inhalation dose was found to be 1.8 ± 0.7 mSv/y. The estimated values of the annual effective dose were found to be 1.2 ± 0.5 mSv/y and 0.5 ± 0.3 mSv/y, respectively. The estimated values of radiation doses suggest no important health risk due to exposure of radon, thoron and progeny in the study area. The contribution of indoor thoron and its progeny to total inhalation dose ranges between 13–52% with mean value of 30%. Thus thoron cannot be neglected when assessing radiation doses.